2020
DOI: 10.1111/bjep.12372
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the process of epistemic change: The role of epistemic volition

Abstract: Background. Many interventions on epistemic beliefs (i.e., individual beliefs about knowledge and knowing) are based on Bendixen and Rule's Integrative Model for Personal Epistemology Development. Empirically, however, the model is still insufficiently validated. This is especially true for its epistemic volition componenta will or desire to actively change one's beliefs. Aims. To experimentally scrutinize the role of epistemic volition, we investigated (incremental) effects on epistemic change of an epistemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…For their inquiry, students were presented with four fictitious search engine results pages. According to Kerwer et al (2021), "each of these four outputs contained four fictitious results-two high-quality and two low-quality sites, while the valence (i.e., the supposed direction of the relationship-achievement motivation increases or decreases the risk of heart diseases) differs within each pair (e.g., within high quality sites). For each output, subjects chose which site they would like to inspect in more detail during a later stage of the study" (p. 12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For their inquiry, students were presented with four fictitious search engine results pages. According to Kerwer et al (2021), "each of these four outputs contained four fictitious results-two high-quality and two low-quality sites, while the valence (i.e., the supposed direction of the relationship-achievement motivation increases or decreases the risk of heart diseases) differs within each pair (e.g., within high quality sites). For each output, subjects chose which site they would like to inspect in more detail during a later stage of the study" (p. 12).…”
Section: Methodsmentioning
confidence: 99%
“…Intervention components for doubt and volition were identical to those employed by Kerwer et al (2021), and were administered in their computer-based versions (see Kerwer & Rosman, 2020). All intervention materials were specifically tailored to psychology students and revolved around a psychological topic (gender stereotyping in schools).…”
Section: Intervention Componentsmentioning
confidence: 99%
“…“Disentangling the process of epistemic change: The role of epistemic volition” (Kerwer et al, 2020; in British Journal of Educational Psychology )…”
Section: Applications Of Registered Reportsmentioning
confidence: 99%
“…Moreover, people's beliefs about the nature of knowledge and learning are of effect on variables such as academic performance, new information processing methods, their level of understanding, source of control, strategies used in the study, higher order thinking, self-regulatory processes, approaches of problem solving and the time and effort they spend for learning (9-14, 15, 16, 17, 18, 19). In particular, researches on the intertwined relationship between the use of multiple sources and the mental processes associated with epistemic beliefs have been very fruitful in recent decades (20,21,22,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Ferguson et al (2013) found that the data have satisfactory psychometric properties, and factor analysis confirmed these three justification dimensions in students from other countries (42). Some researchers have also used qualitative methods to examine beliefs and epistemicchange (24).…”
Section: Introductionmentioning
confidence: 99%